2015
DOI: 10.1021/acsami.5b04336
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Hierarchical Formation of Conjugated 3D Cobalt Oxide Nanobead–CNT–Graphene Nanostructure Using Microwaves for High-Performance Supercapacitor Electrode

Abstract: Here we report the electrochemical performance of a interesting three-dimensional (3D) structures comprised of zero-dimensional (0D) cobalt oxide nanobeads, one-dimensional (1D) carbon nanotubes and two-dimensional (2D) graphene, stacked hierarchically. We have synthesized 3D self-assembled hierarchical nanostructure comprised of cobalt oxide nanobeads (Co-nb), carbon nanotubes (CNTs), and graphene nanosheets (GNSs) for high-performance supercapacitor electrode application. This 3D self-assembled hierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(60 citation statements)
references
References 53 publications
1
57
2
Order By: Relevance
“…In recent years, metal oxide nanoparticles especially metal oxide/CNT nanocomposites have attracted a good deal of persistent interest because of their unique chemical, physical, electrical, and thermal properties [4][5][6]. These materials are widely used in several areas, including chemistry, physics, material science, biology, medicine, and environment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, metal oxide nanoparticles especially metal oxide/CNT nanocomposites have attracted a good deal of persistent interest because of their unique chemical, physical, electrical, and thermal properties [4][5][6]. These materials are widely used in several areas, including chemistry, physics, material science, biology, medicine, and environment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [172] reported an interesting work about the fabrication of 3D hierarchical structure composed of 0D Co 3 O 4 nanobeads, 1D carbon nanotubes (CNTs), and 2D graphenes (GNSs) via an easy ultrafast microwave irradiation method for high performance supercapacitor electrode. In this unique structure, Co 3 O 4 nanobeads are anchored on CNTs and the CNTs are grown on GNSs, leading to a good electrochemical performance.…”
Section: Composites Of Carbon Materials and Tmosmentioning
confidence: 99%
“…Upcycling is the process of converting waste materials into something useful and more valuable. And CNTs have a wide application in many¯elds [11][12][13] on account of their desirable mechanical, optical, electrical and thermal properties. 14,15 Hence, transforming waste polymers into high value-added CNTs is desirable.…”
Section: Introductionmentioning
confidence: 99%